THE DIASPORIC LIFE OF PAKISTANI-AMERICAN GIRL IN DUR E AZIZ AMNA’S AMERICAN FEVER - Sugiarto, Diktha Aurilya Ghardini Novi; Astutiningsih, Irana; Sukarno, Sukarno (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2023)
American Fever is a novel that tells the story of a high school girl from Pakistan named Hira who joins a student exchange program for 1 year in America. As a diaspora subject, Hira's arrival to America raises issues related to identity. Hira is seen as a stranger and she also has difficulty to adapt in a new environment with the different culture from Pakistan. Therefore, Bhabha's theory of postcolonialism is applied in this study. This thesis aims to reveal the cultural strategy undertaken by Hira to survive in America by connecting with contextual conditions and to find out the author's views on diaspora issues through the novels she wrote. This thesis is a critical-qualitative study. Primary data are from novels and secondary data are from the internet, books and articles. The results of the analysis of this novel show that as a diaspora subject, Hira experiences a phase of 'unhomeliness' caused by her first arrival to America. Then, to overcome this condition, Hira applies a cultural adjustment known as mimicry. The result of mimicry is that Hira has hybrid identity, as a Pakistani and an American. Amna, as the author of this novel conveyed her idea regarding the issue of diaspora that he experienced in 2008 that diaspora subjects will experience 3 phases namely 'unhomeliness', mimicry, and hybridity when they come to the host country. In conclusion, Bhabha's postcolonial theory is related to the events in American Fever which are the depiction of the author's personal experience as a diaspora subject in the past.